Factors influencing transfer of training among employees in Petronas Dagangan Berhad, Kuala Lumpur / Fatin Iylia Ajamik - Ajamik, Fatin Iylia (Faculty of Business and Management, 2020)
Nowadays, every organization has been given lots of efforts in maximising the effectiveness of the employees’ performance in the workplace by conducting the training programme to enhance their knowledge, skills and abilities. However, many organizations have reported that there is a failure in transferring the training knowledge to the actual job area. Thus, this study aimed to explore the factors of work environment, trainee characteristics and training design on their skills in transferring the newly knowledge. To fill this gap in knowledge, this study investigated the relationship between factors influencing the transfer of training among employees or staffs in Petronas Dagangan Berhad. This study has been conducted and the data being collected by questionnaires that involved 304 respondents. Sampling technique that been used in this study is non-probability sampling which specifically in convenience sampling technique. The data that had been collected was then evaluated by using Statistical Package for the Social Science (SPSS) Software version 25. Descriptive analysis, reliability analysis, Pearson’s correlation analysis and multiple regression analysis were used in this study to identify the relationships between work environment, trainee characteristics and training design towards transfer of training. Based on findings, only two independent variables which are work environment and trainee characteristics are significant related with transfer of training meanwhile training design is not significant with transfer of training and this study shows that work environment as the greatest contribution to the influence in transfer of training.